Students' Spatial Ability in GeoGebra-Assisted Mathematics Learning: A Systematic Literature Review - Amanda Putri Meirani; St Budi Waluya; Zaenuri Zaenuri; Walid Walid (Program Studi Pendidikan Matematika, FSTT, Universitas Pendidikan Mandalika, 2026)
Spatial ability is a curriculum requirement that must be accommodated in mathematics learning. This study aims to systematically examine students' spatial abilities in GeoGebra-assisted mathematics learning. The study was conducted using the Systematic Literature Review (SLR) method on 12 research articles from 2020–2025 and obtained through the Google Scholar and Crossref database with the help of the Publish or Perish application. The results of the study indicate that the research trend of students' spatial abilities in GeoGebra-assisted mathematics learning has increased in the last five years with a focus on the application of various innovative learning models such as Realistic Mathematics Education (RME), Problem-Based Learning (PBL), Project-Based Learning (PjBL), Van Hiele, and Discovery Learning. In conclusion, the integration of GeoGebra in mathematics learning is flexible, interactive, and relevant as an innovative strategy to strengthen students' spatial abilities.